Cultural context shapes the selection and adaptiveness of interpersonal emotion regulation strategies - Prüßner, Luise; Altan-Atalay, Ayşe (Emotion, 2025)
In everyday life, we commonly experience, express, and regulate our emotions in interpersonal contexts. However, much of the existing research on utilizing others for modulating one’s emotions has focused on Western, individualistic cultures, leaving a significant gap in understanding how the selection and adaptiveness of interpersonal emotion regulation (IER) strategies vary across cultural contexts. This cross-national comparison study aims to bridge this gap by examining intrinsic IER in 1,187 participants from Turkey and Germany, which are characterized by different cultural norms, values, and socialization practices regarding emotional experience and expression. All participants completed measures of intrinsic IER strategies alongside measures of adaptive outcomes, including depression, anxiety, negative affect, and positive affect. The results revealed cross-national differences between Turkish and German individuals in terms of the intrinsic IER strategies most frequently selected and their associations with depression, anxiety, negative affect, and positive affect. These findings emphasize the significance of cultural context in intrinsic IER and offer insights into the conditions under which these strategies are linked to adaptive outcomes. By recognizing the cultural nuances in how people navigate their emotions via social interactions, clinicians and researchers can develop more culturally sensitive interventions tailored to the specific needs of individuals in diverse cultural contexts. (PsycInfo Database Record (c) 2024 APA, all rights reserved)